Foundations of quality risk management : a practical approach to effective risk-based thinking - Moon, Jayet (Quality Press, 2020)
"A comprehensive reference and thorough introduction to risk management and risk-based thinking from a quality perspective and using quality tools"-- Provided by publisher.
Keywords: Risk management.; Quality control.; elektronické knihy; electronic books